Creating Radiology Line Art With Photoshop Tools and Filters - Mahesh Thapa; Sandeep Vaidya; Manjiri Dighe; Michael Richardson (Association of American Medical Colleges, 2011)
Abstract In this resource, we outline a method to convert digital radiologic images into line art. Our novel approach primarily utilizes a stylizing filter and the levels tool in Photoshop. We present the steps as a detailed tutorial, complete with sample images, to guide the learner through the process. In addition, we also include a screencast (movie) showing all the steps and resulting effects. The method described is quick and does not require employing professional medical illustrators or buying stock digital images, which can become very expensive. In addition to the example image of a knee, we also include three other images for the learner to examine and play with. These images are an axial CT scan of the temporal bone, a coronal reconstruction of a body CT scan, and a mid-sagittal MRI slice of a brain.